PLANNING THE ESTABLISHMENT OF THE NAIL ART STUDIO “ELINAILED” BUSINESS - Anjelin Putri Sukma Dewi; Nurina Ayuningtyas; Dwi Atmanto (Journal of Social and Economics Research, 2025)
Business plan “Elinailed” is a business that focuses on nail art services that prioritize excellent service, comfort and quality. The services offered include nail art, manicure, pedicure, NFC LED Nail, and exclusive nail care. This research aims to analyze the feasibility of establishing Elinailed business planning as a nail art studio by identifying market, marketing, operational planning, and financial aspects. It is expected that this business will be able to compete in the increasingly tight beauty industry. This research also evaluates financial aspects such as Payback Period (PP), Net Present Value (NPV), Internal Rate of Return (IRR), Break Event Point (BEP), Benefit and Cost Ratio (B/C Ratio) or Profitability Index to ensure the sustainability of this business. The results indicate that “Elinailed” has a significant market opportunity with a wide range of target consumers, especially among women who pay attention to their appearance. With the implementation of appropriate marketing strategies and effective management, Elinailed is expected to show sustainable growth and have a real positive impact on the beauty industry.